On the impact of independence of irrelevant alternatives: The case of two-person NTU games - Bezalel Peleg; Peter Sudhölter; José M. Zarzuelo (SERIEs - Journal of the Spanish Economic Association, 2012)
On several classes of n-person NTU games that have at least one Shapley NTU value, Aumann characterized this solution by six axioms: Non-emptiness, efficiency, unanimity, scale covariance, conditional additivity, and independence of irrelevant alternatives (IIA). Each of the first five axioms is logically independent of the remaining axioms, and the logical independence of IIA is an open problem. We show that for n = 2 the first five axioms already characterize the Shapley NTU value, provided that the class of games is not further restricted. Moreover, we present an example of a solution that satisfies the first five axioms and violates IIA for two-person NTU games (N, V ) with uniformly p-smooth V(N).
Keywords: C71; 330; NTU game; Shapley NTU value; positive smoothness; Non-transferable Utility Games; Shapley-Wert; Kooperatives Spiel; Theorie